Multi-metal co-doped and coated positive electrode material as well as preparation method and application thereof
By ion doping lithium-containing layered oxides with alkali metal ions and high-valent metal ions, a positive electrode material with multi-metal co-doped coated is solved, and the cyclic stability and magnification of high-nickel ternary positive electrode materials under high voltage is solved. The problem of poor performance achieves efficient modification of the material and improves conductivity and cycle stability.
Patent Information
- Application Number
- CN202411593305.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The existing layered oxide positive electrode materials, especially high-nickel ternary positive electrode materials, have poor cycling stability, poor rate performance at high voltages, and severe surface side reactions, resulting in performance decay.
By ion doping the lithium-containing layered oxide with alkali metal ions and high-valent metal ions with a compound valence ≥3, a polymetal co-doped coated positive electrode material is formed. This method promotes the doping of high-valent metal ions into the internal doping by widening the surface lattice spacing, forming a heterostructure layer, stabilizing the material structure, and reducing side reactions.
The cyclic stability and rate performance of the positive electrode material under high voltage are improved, the side reaction between the material and the electrolyte is reduced, irreversible phase change is suppressed, and the conductivity and cyclic stability are greatly improved.
Smart Images

Figure CN119480976A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a multi-metal co-doped and coated positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion battery is a simple and efficient energy storage system. As an important energy storage technology to cope with the increasingly serious energy crisis, it is one of the important development strategies of various countries including my country, and has always been a research hotspot in academia and industry. Lithium-ion battery has the highest energy density and power density among many energy storage devices. It also has many advantages such as high output voltage, no memory effect, low self-discharge, high energy efficiency, long cycle life and wide operating temperature range.
[0003] As one of the most critical components of lithium-ion batteries, positive electrode materials are the key to achieving high energy density. Among positive electrode materials, LiCoO2 is the first lithium-containing positive electrode material to enter people's field of vision. It has a high volume energy density and a long cycle life. However, the high price of the Co element limits its application to smaller 3C devices. In order to solve this problem and meet the needs of larger energy storage devices such as electric vehicle batteries, ternary positive electrode materials have been derived. Ternary positive electrode materials are positive electrode materials obtained by replacing part of the Co element in LiCoO2 with Ni, Mn or Al. The more common ones are LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), etc. With the increase of Ni content, the ternary material can show higher reversible capacity, but it will be accompanied by a decrease in cycle performance, rate performance and safety performance. Generally speaking, researchers call NCM ternary materials with Ni content greater than 0.5 high-nickel NCM ternary materials.
[0004] The high capacity of high-nickel materials is very attractive. At present, following NCM622, NCM811 materials have also entered the commercialization stage, but there are still many problems to be solved. Specifically, the active surface chemistry leading to more side reactions is a major problem of high-nickel positive electrode materials. The surface of high-nickel materials is easy to generate contamination groups. When exposed to air alone, they will easily react with CO2 and H2O to generate LiOH and Li2CO3, resulting in a significant increase in the alkalinity of the material surface, increasing the viscosity of the slurry, and even causing the coating step to fail in severe cases. When the high-nickel ternary material works at a high voltage, it will react violently with the electrolyte, resulting in the loss of active substances, thereby increasing the electrochemical impedance during the battery charging and discharging process. And during the charging and discharging process, the secondary spherical ternary positive electrode material expands or shrinks to a large extent, resulting in cracks, causing the active substances to fall off, resulting in performance degradation. In response to these problems of NCM ternary high-nickel materials, researchers have adopted many modification methods to improve the cycle performance and rate performance of the materials. Among them, the most common method is still element doping to stabilize the structure and surface coating to inhibit interface side reactions. This type of method has similar modification effects in other layered oxide positive electrode materials. Generally, element doping can only achieve better results by doping the raw materials for preparing positive electrode materials. However, it is difficult to incorporate transition metal elements into the lattice phase of the material when doping finished positive electrode materials. The doped elements are mainly enriched on the surface, which has limited effect on improving the performance of the material.
[0005] In summary, the layered oxide positive electrode materials currently on the market, especially the high-nickel ternary positive electrode materials, face the problems of unstable structural skeleton under high voltage and violent surface side reactions leading to performance degradation. High-nickel ternary materials have high energy density and relatively low cost, so the market potential is huge. If we want to realize the potential of these materials, these problems need to be solved urgently.
[0006] Chinese patent CN114784248B discloses a coated modified high-nickel ternary positive electrode material, which is prepared by mixing metal oxygen-containing acid powder with a high-nickel ternary positive electrode material to obtain a powder-coated high-nickel ternary positive electrode material; then annealing the powder-coated high-nickel ternary positive electrode material to obtain a coated modified high-nickel ternary positive electrode material; Chinese patent document CN118299544A discloses a modified high-nickel ternary positive electrode, which dopes fluorine into a precursor structure of a high-nickel ternary positive electrode material to form a single-doped precursor; calcining a mixture of the single-doped precursor, a tellurium source and a lithium source for the first time to obtain a co-doped positive electrode material at different sites; washing the co-doped positive electrode material at different sites with water, adding a vanadium source during the washing process, followed by drying and a second calcination to obtain a modified high-nickel ternary positive electrode material in which tellurium and fluorine are co-doped at different sites and coated with lithium vanadate LiV2O4. Although these existing modification strategies can improve and enhance the cycle stability of lithium-ion positive electrode materials to a certain extent, they still cannot meet people's needs, especially the modification effect on high-nickel ternary positive electrode materials is poor. Summary of the invention
[0007] The technical problem solved by the present invention is to overcome the defects of poor cycle stability and poor rate performance of layered positive electrode materials under high voltage in the prior art, and provide a multi-metal co-doped coated positive electrode material and a preparation method and application. The multi-metal co-doped coated positive electrode material prepared by the present invention has excellent cycle stability, rate performance and conductivity; and the preparation method is simple, efficient and easy to mass produce.
[0008] The present invention adopts alkali metal ion A to form lithium-containing layered oxide. n+ and high-valent metal ions B n+ During the reaction, the alkali metal ions will react with the Li + Ion exchange occurs between metal ions, so that the alkali metal A with a larger ionic radius n+ Ions are doped into the surface of lithium-containing layered oxides, thereby widening the surface lattice spacing of lithium-containing layered oxides and promoting the high-valent metal B n+ Doping the lithium-containing layered oxide makes it easier for high-valent metal ions to penetrate into the lattice. The two synergistically coat to achieve a deeper degree of modification, thereby further stabilizing the crystal structure of the material and inhibiting the diffusion of lattice oxygen from the bulk phase to the surface after oxidation. Furthermore, during use, it can also reduce the side reactions between the material and the electrolyte, inhibit irreversible phase changes, and greatly improve the conductivity and cycle stability of the lithium-containing layered oxide. Production personnel do not need to change the raw materials, and can directly use the prepared positive electrode materials or commercial positive electrode materials for modification. The operation steps are simple and efficient, low cost, and low requirements for process technology.
[0009] The present invention solves the above technical problems through the following technical solutions:
[0010] The present invention provides a multi-metal co-doped coated positive electrode material, comprising a substrate and a coating layer located on the surface of the substrate, wherein the substrate is a lithium-containing layered oxide, and the coating layer is a lithium-containing layered oxide and an alkali metal ion A. n+ and high-valent metal ions B with valence ≥ 3 n+ "The alkali metal-based oxide heterostructure layer containing high-valent metals is formed by ion doping and structural reconstruction. The internal and external structural lattices are coherent and there is no obvious interface.
[0011] In the present invention, the formation principle of the heterogeneous structure layer is to use alkali metal ions A with a larger ionic radius. n+ Doping broadens the lattice spacing on the surface of the lithium-containing layered oxide, assisting the high-valent metal ion B n+ By performing deeper doping, the heterostructure layer can stabilize the structure of the material under high voltage, thereby inhibiting the irreversible structural changes and interface side reactions of the positive electrode material under high voltage.
[0012] In the present invention, the internal and external structures being lattice coherent means that the internal and external structures are similar and are both layered structures.
[0013] In the present invention, the coating layer may have a thickness of 2-10 nm.
[0014] In the present invention, the ratio of the sum of the masses of the alkali metal and the high-valent metal with a valence ≥ 3 in the heterostructure layer to the mass of the lithium-containing layered oxide is preferably (0.002-0.6):1, more preferably (0.02-0.2):1, for example 0.01:1, 0.017:1, 0.019:1, 0.02:1 or 0.04:1.
[0015] In the present invention, the ratio of the mass of the alkali metal in the heterogeneous structure layer to the mass of the lithium-containing layered oxide is preferably (0.001-0.3):1, and more preferably (0.001-0.2):1.
[0016] In the present invention, the ratio of the mass of the high-valent metal with a valence ≥ 3 in the heterostructure layer to the mass of the lithium-containing layered oxide is preferably (0.001-0.3):1, more preferably (0.001-0.2):1.
[0017] In the present invention, the chemical formula of the lithium-containing layered oxide is generally Li x M y Q2 indicates that M is one or more of Ni, Co, Mn, Cu, Fe, Zn, Al and Cr, and Q is one or more of O, F, Cl, S, Se and N.
[0018] Wherein, in the lithium-containing layered oxide, preferably, 0<x<2, for example, 1 or 1.2.
[0019] Wherein, in the lithium-containing layered oxide, preferably, 0<y≤1, for example, 0.8 or 1.
[0020] In the present invention, the lithium-containing layered oxide can be conventional in the art, preferably one or more of lithium cobalt oxide, ternary positive electrode material and lithium-rich manganese material, more preferably lithium-rich manganese material. Among them, the ternary positive electrode material can be conventional in the art, such as Ni90 high-nickel ternary positive electrode material, NCM523. The lithium-rich manganese material can be, for example, Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2.
[0021] In the present invention, the lithium-containing layered oxide can be obtained from conventional commercial sources or synthesized by conventional high-temperature solid phase method, sol-gel method, hydrothermal synthesis method, or coprecipitation method in the art.
[0022] In the present invention, the alkali metal ion A n+ Preferably Na + and / or K + .
[0023] In the present invention, the high-valent metal ion with a valence of ≥3 is preferably a transition metal ion with a valence of ≥3 and / or a main group metal ion with a valence of ≥3, and more preferably a transition metal ion with a valence of ≥3. The transition metal ion with a valence of ≥3 is preferably Ti 4+ 、Zr 4+ 、Ru 4+ , Nb 5+ 、 5+ 、Mo 6+ and W 6+ The main group metal ion with a valence of ≥3 is preferably In 3+ Sn 4+ and Sb 3+ One or more of .
[0024] The present invention also provides a method for preparing a multi-metal co-doped coated positive electrode material, which comprises the following steps:
[0025] Method 1:
[0026] (1) Li-containing layered oxide Li x M yA mixture of Q2 and a compound containing an alkali metal A is annealed to obtain a precursor; wherein the mass ratio of the alkali metal in the compound containing the alkali metal A to the lithium-containing layered oxide is (0.001-0.3):1;
[0027] (2) the precursor and the high-valent metal ion B having a valence of ≥3 n+ A mixture of a metal salt and / or an oxide containing a high-valent metal B with a valence ≥3 is annealed; wherein the high-valent metal ion B containing a valence ≥3 n+ The mass ratio of the high-valent metal with a valence ≥ 3 in the metal salt and / or the oxide containing the high-valent metal B with a valence ≥ 3 to the lithium-containing layered oxide is (0.001-0.3): 1;
[0028] Or, method 2:
[0029] Lithium-containing layered oxide Li x M y Q2. Compounds containing alkali metal A and compounds containing high-valent metal ions B with a valence ≥ 3 n+ wherein the mass ratio of the alkali metal in the compound containing the alkali metal A to the lithium-containing layered oxide is (0.001-0.3):1, and the high-valent metal ion B containing the valence ≥3 is 1:1. n+ The mass ratio of the high-valent metal with a valence ≥3 in the metal salt and / or the oxide containing the high-valent metal B with a valence ≥3 to the lithium-containing layered oxide is (0.001-0.3):1.
[0030] In the present invention, the lithium-containing layered oxide is as described above and will not be described in detail herein.
[0031] In the present invention, the alkali metal A is preferably Na and / or K.
[0032] In the present invention, the compound containing alkali metal A is preferably one or more of a metal salt containing alkali metal A, a base containing alkali metal A and an oxide containing alkali metal A, for example, a metal salt containing alkali metal A or a base containing alkali metal A.
[0033] Wherein, the salt containing alkali metal A may be sodium carbonate, sodium bicarbonate, potassium carbonate or potassium bicarbonate. The base containing alkali metal A may be sodium hydroxide or potassium hydroxide. The oxide containing alkali metal A may be sodium oxide or potassium oxide.
[0034] In the present invention, the mass ratio of the alkali metal in the compound containing the alkali metal A to the lithium-containing layered oxide is preferably (0.001-0.2):1, such as 0.005:1, 0.01:1, 0.02:1, 0.05:1 or 0.1:1.
[0035] In the present invention, the high-valent metal with a valence ≥3 is preferably a transition metal with a valence ≥3 and / or a main group metal with a valence ≥3, and more preferably a transition metal with a valence ≥3.
[0036] Among them, the transition metal with a valence ≥ 3 is preferably one or more of Ti, Zr, Ru, Nb, Ta, Mo and W.
[0037] Wherein, the main group metal with a valence ≥ 3 is preferably one or more of In, Sn and Sb.
[0038] In the present invention, the high-valent metal ion B containing a valence ≥ 3 n+ The metal salt is preferably a high-valent metal ion B containing a valence ≥ 3 n+ The alkoxide and / or ammonium salt of zirconate, such as tetrabutyl zirconate, tetrabutyl titanate, ammonium niobium oxalate, ammonium molybdate, ammonium tungstate, antimony nitrate or indium nitrate. The oxide containing the high-valent metal B with a valence of ≥3 is, for example, tungsten oxide, molybdenum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide, tin dioxide or antimony oxide.
[0039] In the present invention, the high-valent metal ion B containing a valence ≥ 3 n+ The mass ratio of the high-valent metal with a valence ≥ 3 in the metal salt and / or the oxide containing the high-valent metal B with a valence ≥ 3 to the lithium-containing layered oxide is preferably (0.001-0.2):1, for example 0.005:1, 0.007:1, 0.009:1, 0.01:1, 0.02:1 or 0.1:1.
[0040] Method 1, in step (1), the annealing temperature is preferably 400-1000°C, more preferably 500-800°C, such as 550°C, 650°C or 700°C. The annealing time can be 4-24h, preferably 6-24h, such as 10h, 15h or 20h. The rate of heating to the annealing temperature is preferably 1-10°C / min, such as 5°C / min. The annealing is generally carried out in air or oxygen atmosphere.
[0041] Method 1: In step (1), the mixture is preferably subjected to micro-water mixing, solid phase mixing or liquid phase mixing before the annealing treatment.
[0042] Wherein, the micro-water mixing preferably comprises the following steps: stirring and evaporating the solution containing the mixture. The solvent in the solution may be conventional in the art, such as one or more of deionized water, ethanol, acetone, DMF, ethylenediamine and triethylamine. The amount of the solvent may be conventional in the art, generally sufficient to immerse the solid material. Preferably, the ratio of the mass of the lithium-containing layered oxide to the volume of the solvent may be (0.5-2) g / mL, such as 1 g / mL, 1.5 g / mL or 2 g / mL. The evaporation process is preferably carried out under stirring.
[0043] The solid phase mixing preferably comprises the following steps: grinding the mixture for 10-100 min, such as 30 min or 50 min.
[0044] Wherein, the liquid phase mixing preferably includes the following steps: the solution containing the mixture is fully stirred at 15-200°C, and then solid-liquid separation and drying are performed. The solvent in the solution may be conventional in the art, preferably one or more of deionized water, ethanol, acetone, DMF, ethylenediamine and triethylamine. The amount of the solvent in the solution may be conventional in the art, and preferably, the ratio of the mass of the lithium-containing layered oxide to the volume of the solvent may be (0.2-1) g / mL, for example, 0.5 g / mL. The stirring time may be 0.5-48h, preferably 12-24h. The solid-liquid separation method may be conventional in the art, such as suction filtration. The drying method may be conventional in the art, such as drying.
[0045] When the mixture is subjected to the micro-water mixing or the solid phase mixing, the mass ratio of the alkali metal in the compound containing the alkali metal A to the lithium-containing layered oxide is preferably (0.001-0.1):1, for example, 0.005:1, 0.01:1, 0.02:1, 0.05:1 or 0.1:1.
[0046] When the mixture is subjected to the liquid phase mixing, the mass ratio of the alkali metal in the compound containing the alkali metal A to the lithium-containing layered oxide is preferably (0.05-0.2):1, such as 0.05:1 or 0.1:1.
[0047] When the mixture is mixed in liquid phase, part of the compound containing alkali metal A will remain in the solution after solid-liquid separation, resulting in a waste of raw materials. Therefore, the amount of the compound containing alkali metal A can be appropriately increased.
[0048] Method 1: In step (1), according to the common practice in the art, after the annealing treatment, it is generally necessary to cool naturally to room temperature.
[0049] In step (2) of method 1 and / or method 2, the mixture is preferably subjected to slight water mixing, solid phase mixing or liquid phase mixing before annealing. The operation and conditions of slight water mixing, solid phase mixing and liquid phase mixing are as described above and will not be repeated here. In some preferred embodiments, when the raw material is the high-valent metal ion B containing a valence ≥ 3 n+ When the raw material is a metal salt, the mixture is slightly mixed with water before the annealing; when the raw material is an oxide of the high-valent metal B containing a valence ≥ 3, the mixture is solid-phase mixed before the annealing.
[0050] When the mixture is subjected to the micro-water mixing or the solid phase mixing, the high-valent metal ion B containing a valence of ≥3 n+ The mass ratio of the high-valent metal with a valence ≥ 3 in the metal salt and / or the oxide containing the high-valent metal B with a valence ≥ 3 to the lithium-containing layered oxide is preferably (0.005-0.1):1, for example 0.005:1, 0.01:1, 0.02:1, 0.05:1 or 0.1:1.
[0051] When the mixture is subjected to the liquid phase mixing, the high-valent metal ion B containing a valence ≥ 3 n+ The mass ratio of the high-valent metal with a valence ≥ 3 in the metal salt and / or the oxide containing the high-valent metal B with a valence ≥ 3 to the lithium-containing layered oxide is preferably (0.05-0.2):1, for example 0.05:1 or 0.1:1.
[0052] Method 1, in step (2), the annealing temperature may be 200-1000°C, preferably 400-800°C, such as 550°C, 650°C or 700°C. The annealing time may be 0.5-24h, preferably 8-24h, such as 10h, 15h or 20h. The rate of heating to the annealing temperature is preferably 1-10°C / min, such as 5°C / min.
[0053] In method 2, the annealing temperature may be 300-1000°C, preferably 400-800°C, such as 550°C, 650°C or 700°C. The annealing time may be 0.5-24h, preferably 8-24h, such as 10h, 15h or 20h. The rate of heating to the annealing temperature is preferably 1-10°C / min, such as 5°C / min.
[0054] In step (2) of method 1 and / or method 2, the annealing is generally performed in air or oxygen atmosphere. When the lithium-containing layered oxide is a ternary cathode material with a high Ni content or a lithium-manganese-rich material, the annealing is preferably performed in an oxygen atmosphere.
[0055] In the present invention, when the method is adopted, the prepared multi-metal co-doped coated positive electrode material has more uniform coating, deeper doping degree and better cycle stability.
[0056] The present invention also provides a multi-metal co-doped and coated positive electrode material prepared by the preparation method as described above.
[0057] In the present invention, the multi-metal co-doped coated positive electrode material preferably comprises a substrate and a coating layer located on the surface of the substrate, wherein the substrate is a lithium-containing layered oxide, and the coating layer is a lithium-containing layered oxide and an alkali metal ion A. n+ and high-valent metal ions B with valence ≥ 3 n+ "The alkali metal-based oxide heterostructure layer containing high-valent metals is formed by ion doping and structural reconstruction. The internal and external structural lattices are coherent and there is no obvious interface.
[0058] The present invention also provides an application of the multi-metal co-doped and coated positive electrode material as described above in a lithium ion battery.
[0059] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0060] The reagents and raw materials used in the present invention are commercially available.
[0061] The positive and progressive effects of the present invention are:
[0062] (1) The multi-metal co-doped and coated lithium ion battery positive electrode material prepared by the present invention has excellent cycle stability and rate performance; the method can alleviate the side reaction between the material and the electrolyte surface, and realize the improvement of the electrochemical performance of the material under high voltage;
[0063] (2) The preparation method of the present invention is simple, efficient, low-cost, has low requirements for process technology, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a scanning electron microscope photograph of the Na-W co-coated high nickel cathode material prepared in Example 1;
[0065] Figure 2 A transmission electron microscope photograph of the Na-W co-coated high nickel cathode material prepared in Example 1;
[0066] Figure 3 The X-ray diffraction pattern of the powder of the Na-W co-coated high nickel cathode material prepared in Example 1;
[0067] Figure 4The charge and discharge curves of the Ni90 high-nickel ternary positive electrode material of Comparative Example 1 and the Na-W co-coated high-nickel positive electrode material prepared in Example 1 at 3-4.3V;
[0068] Figure 5 Comparison of the half-cell cycle performance at 3-4.3V between the Na-W co-coated high nickel cathode material (Na-W@Ni90) prepared in Example 1 and the Ni90 high nickel ternary cathode material (Ni90) of Comparative Example 1;
[0069] Figure 6 Comparison of the half-cell cycle performance at 3-4.6V between the Na-W coated modified lithium cobalt oxide material (Na-W@LCO) prepared in Example 12 and the uncoated lithium cobalt oxide positive electrode material (LCO) in Comparative Example 3;
[0070] Figure 7 Comparison of the soft pack cycle performance at 3-4.5V between the Na-W coated modified lithium cobalt oxide material (Na-W@LCO) prepared in Example 12 and the uncoated lithium cobalt oxide positive electrode material (LCO) in Comparative Example 3;
[0071] Figure 8 The half-cell cycle performance of the Na-Zr coated modified lithium-rich manganese positive electrode material (Na-Zr@LLMO) prepared in Example 16 and the uncoated lithium-rich manganese positive electrode material (LLMO) in Comparative Example 4 at 2-4.8V is compared.
[0072] Fig. 9 The half-cell cycle performance of the Na-Zr coated and modified high-nickel positive electrode materials prepared in Examples 19 and 20 and the uncoated high-nickel positive electrode material in Comparative Example 1 at 2-4.8V is compared. DETAILED DESCRIPTION
[0073] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0074] The molecular formula of ammonium tungstate used in the following examples and comparative examples is (NH4) 10 W 12 O 41 ·xH2O, with a molecular weight of 3060.46 g / mol; the molecular formula of ammonium niobium oxalate is C4H4NNbO9·xH2O, with a molecular weight of 302.98 g / mol.
[0075] Example 1
[0076] Weigh 10g of Ni90 high-nickel ternary positive electrode material (Rongbai S90E) and 0.23g of sodium carbonate into a beaker, add 10mL of water, heat and stir until evaporated, and then place the obtained mixture in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-doped precursor; then place all the Na-doped precursors in 10mL of an aqueous solution containing 0.14g of ammonium tungstate, heat and stir until evaporated, and place it in a tubular furnace in an oxygen atmosphere for calcination again at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-W synergistically coated high-nickel positive electrode material.
[0077] Example 2
[0078] Weigh 10g of Ni90 high-nickel ternary positive electrode material (Rongbai S90E) and 0.23g of sodium carbonate into a beaker, add 10mL of water, heat and stir until evaporated, and then place the obtained mixture in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, keep warm at 550°C for 10h, and naturally cool to room temperature to obtain a Na-doped precursor; then place all the Na-doped precursors in 10mL of an aqueous solution containing 0.14g of ammonium tungstate, heat and stir until evaporated, and place it in a tubular furnace in an oxygen atmosphere for calcination again at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-W synergistically coated high-nickel positive electrode material.
[0079] Example 3
[0080] Weigh 10g of Ni90 high-nickel ternary positive electrode material (Rongbai S90E) and 0.23g of sodium carbonate into a beaker, add 10mL of water, heat and stir until evaporated, and then place the obtained mixture in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-doped precursor; then place all the Na-doped precursors in 10mL of an aqueous solution containing 0.14g of ammonium tungstate, heat and stir until evaporated, and place it in a tubular furnace in an oxygen atmosphere for calcination again at a heating rate of 5°C / min, keep warm at 550°C for 10h, and naturally cool to room temperature to obtain a Na-W synergistically coated high-nickel positive electrode material.
[0081] Example 4
[0082] Weigh 10g of Ni90 high-nickel ternary positive electrode material (Rongbai S90E) and 0.23g of sodium carbonate into a beaker, add 10mL of water, heat and stir until evaporated, and then place the obtained mixture in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-doped precursor; then place all the Na-doped precursors in 10mL of an aqueous solution containing 0.14g of ammonium tungstate, heat and stir until evaporated, and place it in a tubular furnace in an oxygen atmosphere for calcination again at a heating rate of 5°C / min, keep warm at 650°C for 20h, and naturally cool to room temperature to obtain a Na-W synergistically coated high-nickel positive electrode material.
[0083] Example 5
[0084] Weigh 10.0g of NCM523 ternary cathode material and 0.17g of sodium hydroxide into a beaker, add 10mL of water, heat and stir until evaporated, then place the obtained mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-doped precursor; then place all the Na-doped precursors in 10mL of an aqueous solution containing 0.14g of ammonium tungstate, heat and stir until evaporated, and finally place the obtained mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-W co-coated ternary cathode material.
[0085] Example 6
[0086] Weigh 10.0g of Ni90 high-nickel ternary positive electrode material and 0.14g of potassium hydroxide into a beaker, add 10mL of water, heat and stir until evaporated, and then place the obtained mixture in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a K-doped precursor; then place all the K-doped precursors in 10mL of an aqueous solution containing 0.14g of ammonium tungstate, heat and stir until evaporated, and place it in a tubular furnace in an oxygen atmosphere for calcination again at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a KW-coated high-voltage ternary positive electrode material.
[0087] Example 7
[0088] Weigh 10.0g of NCM523 ternary cathode material and 0.14g of potassium hydroxide into a beaker, add 10mL of water, heat and stir until evaporated, then place the obtained mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a K-doped precursor; then place all the K-doped precursors in 10mL of an aqueous solution containing 0.14g of ammonium tungstate, heat and stir until evaporated, and place it in a tubular furnace in an oxygen atmosphere and calcine again at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a KW-coated high-voltage ternary cathode material.
[0089] Example 8
[0090] Weigh 10.0g of NCM523 ternary cathode material and 0.14g of potassium hydroxide into a beaker, add 10mL of water, heat and stir until evaporated, then place the obtained mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a K-doped precursor; then place all the K-doped precursors in 10mL of ethanol solution containing 0.31g of tetrabutyl zirconate, heat and stir until evaporated, and place it in a tubular furnace in an oxygen atmosphere and calcine again at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a K-Zr co-coated high-voltage ternary cathode material.
[0091] Example 9
[0092] Weigh 10.0g of NCM523 ternary cathode material and 0.17g of sodium hydroxide into a beaker, add 10mL of water, heat and stir until evaporated, then place the obtained mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-doped precursor; then mix and grind all the Na-doped precursors and 0.055g of tungsten oxide and 0.071g of niobium pentoxide for 30min, and finally place the obtained mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-W / Nb synergistically coated high-voltage ternary cathode material.
[0093] Example 10
[0094] Weigh 10.0g of NCM523 ternary cathode material and 0.17g of sodium hydroxide into a beaker, add 10mL of water, heat and stir until evaporated, then place the obtained mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-doped precursor; then mix and grind all the Na-doped precursors and 0.15g of molybdenum oxide for 30min, and finally place the obtained mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-Mo synergistically coated high-voltage ternary cathode material.
[0095] Embodiment 11
[0096] Weigh 10.0g of NCM523 ternary cathode material and 0.14g of potassium hydroxide into a beaker, add 10mL of water, heat and stir until evaporated, then place the obtained mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a K-doped precursor; then mix and grind all the K-doped precursors and 0.15 molybdenum oxide for 30min, and again place the obtained mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and cool to room temperature to obtain a K-Mo synergistically coated high-voltage ternary cathode material.
[0097] Example 12
[0098] Weigh 10.0 g of lithium cobalt oxide positive electrode material and 0.23 g of sodium carbonate into a beaker, add 10 mL of water, heat and stir until evaporated, then place the obtained mixture in a muffle furnace for calcination at a heating rate of 5 ° C / min, keep warm at 650 ° C for 10 hours, and naturally cool to room temperature to obtain a Na-doped precursor; then place all the Na-doped precursors in 10 mL of an aqueous solution containing 0.14 g of ammonium tungstate, heat and stir until evaporated, and then place the obtained mixture in a muffle furnace for calcination at a heating rate of 5 ° C / min, keep warm at 650 ° C for 10 hours, and cool to room temperature to obtain Na-W coated modified high-pressure lithium cobalt oxide.
[0099] Embodiment 13
[0100] Weigh 10.0g of lithium cobalt oxide positive electrode material and 0.17g of potassium carbonate into a beaker, add 10mL of water, heat and stir until evaporated, then place the obtained mixture in a muffle furnace for calcination at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-doped precursor; then place all the K-doped precursors in 10mL of ethanol solution containing 0.21g of ammonium niobium oxalate, heat and stir until evaporated, then place the obtained mixture in a muffle furnace for calcination at a heating rate of 5°C / min, keep warm at 650°C for 10h, and cool to room temperature to obtain K-Nb coated modified high-pressure lithium cobalt oxide.
[0101] Embodiment 14
[0102] Weigh 10.0g of Ni90 high-nickel ternary positive electrode material and 0.17g of potassium carbonate into a beaker, add 10mL of water, heat and stir until evaporated, then place the mixture in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-doped precursor; then place all the Na-doped precursors in 10mL of ethanol solution containing 0.31g of tetrabutyl zirconate, heat and stir until evaporated, and finally place the mixture in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a K-Zr co-coated high-voltage ternary positive electrode material.
[0103] Embodiment 15
[0104] Weigh 10.0g of NCM523 ternary cathode material and 0.23g of sodium carbonate into a beaker, add 10mL of water, heat and stir until evaporated, then place the mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-doped precursor; then place all the Na-doped precursors in 10mL of an aqueous solution containing 0.21g of ammonium niobium oxalate, heat and stir until evaporated, and finally place the mixture in a tubular furnace in an oxygen atmosphere and calcine at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-Nb synergistically coated high-voltage ternary cathode material.
[0105] Example 16
[0106] Weigh 10.0 g of lithium-rich manganese positive electrode material (Li 1.2 Mn 0.54 Ni 0.13 Co 0.13O2) and 0.23g of sodium carbonate are added to 10mL of water in a beaker, heated and stirred until evaporated, and then the mixture is placed in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, kept at 650°C for 10h, and naturally cooled to room temperature to obtain a Na-doped precursor; all the Na-doped precursors are placed in 10mL of ethanol solution containing 0.31g of tetrabutyl zirconate, heated and stirred until evaporated, and finally the mixture is placed in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, kept at 650°C for 10h, and naturally cooled to room temperature to obtain a Na-Zr co-coated lithium manganese-rich positive electrode material.
[0107] Embodiment 17
[0108] Weigh 10.0 g of lithium-rich manganese positive electrode material (Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2) and 0.23g of sodium carbonate are added to 10mL of water in a beaker, heated and stirred until evaporated, and then the mixture is placed in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, kept at 650°C for 10h, and naturally cooled to room temperature to obtain a Na-doped precursor; then all the Na-doped precursors and 0.13g of tin dioxide are mixed and ground, and finally the obtained mixture is placed in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, kept at 650°C for 10h, and naturally cooled to room temperature to obtain a Na-Sn co-coated lithium manganese-rich positive electrode material.
[0109] Embodiment 18
[0110] Weigh 10.0 g of lithium-rich manganese positive electrode material (Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2) and 0.23g of sodium carbonate are added to 10mL of water in a beaker, heated and stirred until evaporated, and then the mixture is placed in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, kept at 650°C for 10h, and naturally cooled to room temperature to obtain a Na-doped precursor; then all the Na-doped precursors are mixed and ground with 0.065g of tin dioxide and 0.055g of tungsten oxide, and finally the mixture is placed in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, kept at 650°C for 10h, and naturally cooled to room temperature to obtain a Na-Sn / W synergistically coated lithium manganese-rich positive electrode material.
[0111] Embodiment 19
[0112] Weigh 10.0g of Ni90 high-nickel ternary positive electrode material and 0.17g of sodium hydroxide into a beaker, add 10mL of water, heat and stir until evaporated, and then place the mixture in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-doped precursor; then place all the Na-doped precursors in 10mL of ethanol solution containing 0.31g of tetrabutyl zirconate, heat and stir until evaporated, and finally place the mixture in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5°C / min, keep warm at 650°C for 10h, and naturally cool to room temperature to obtain a Na-Zr co-coated high-nickel positive electrode material.
[0113] Embodiment 20
[0114] 10 g of Ni90 high-nickel ternary positive electrode material (Rongbai S90E) was placed in 10 mL of ethanol solution containing 0.17 g of sodium hydroxide and 0.31 g of tetrabutyl zirconate, heated and stirred until evaporated, and then placed in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5 °C / min. The material was kept at 650 °C for 10 h and naturally cooled to room temperature to obtain a Na-Zr co-coated high-nickel positive electrode material.
[0115] Embodiment 21
[0116] Weigh 10g of Ni90 high-nickel ternary positive electrode material (Rongbai S90E) and 1.7g of sodium hydroxide in a beaker, add 20mL of water and stir at room temperature for 30min, then perform vacuum filtration, dry the separated solid and calcine it in a tubular furnace in an oxygen atmosphere at a heating rate of 5℃ / min, keep it at 650℃ for 10h, and cool it down to room temperature naturally to obtain a Na-doped precursor; then place all the Na-doped precursors in a 10mL aqueous solution containing 0.14g of ammonium tungstate, heat and stir until evaporated, and calcine it in a tubular furnace in an oxygen atmosphere again at a heating rate of 5℃ / min, keep it at 650℃ for 10h, and cool it down to room temperature naturally to obtain a Na-W synergistically coated high-nickel positive electrode material.
[0117] Embodiment 22
[0118] Weigh 10g of Ni90 high-nickel ternary positive electrode material (Rongbai S90E) and 0.23g of potassium carbonate for solid phase grinding for 30min, then place the obtained mixture in a tubular furnace in an oxygen atmosphere for calcination at a heating rate of 5℃ / min, keep it at 650℃ for 10h, and naturally cool it to room temperature to obtain a K-doped precursor; then place all the K-doped precursors in 10mL ethanol solution containing 0.71g tetrabutyl titanate, heat and stir until evaporated, and place it in a tubular furnace in an oxygen atmosphere for calcination again at a heating rate of 5℃ / min, keep it at 650℃ for 10h, and naturally cool it to room temperature to obtain a K-Ti synergistically coated high-nickel positive electrode material.
[0119] Comparative Example 1
[0120] Ni90 high nickel ternary positive electrode material.
[0121] Comparative Example 2
[0122] NCM523 ternary positive electrode material.
[0123] Comparative Example 3
[0124] Lithium cobalt oxide positive electrode material.
[0125] Comparative Example 4
[0126] Lithium-rich manganese 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2) positive electrode material.
[0127] Effect Example
[0128] (1) Sample characterization
[0129] Figure 1 This is a scanning electron microscope photograph of the Na-W co-coated high-nickel positive electrode material prepared in Example 1. From the figure, it can be seen that the coated high-nickel ternary positive electrode material is about 1 μm. Figure 2 This is a transmission electron microscope photograph of the Na-W co-coated high-nickel positive electrode material prepared in Example 1. From the figure, it can be seen that there is a heterogeneous structure coating layer on the surface of the high-nickel ternary positive electrode material. The coating layer is mainly generated by the reaction of lithium-containing layered oxides and "alkali metal ions and transition metal ions", and is uniformly coated on the surface of the high-nickel ternary positive electrode material. The internal and external structure lattices are coherent, both are layered structures, and there is no obvious interface. Figure 3 The powder X-ray diffraction pattern of the Na-W co-coated high nickel cathode material prepared in Example 1 is shown in FIG. Figure 1 It can be seen that the high nickel ternary positive electrode material after coating and modification does not show other impurity diffraction peaks.
[0130] (2) Electrochemical performance test
[0131] Half-cell performance test: The electrochemical performance of the prepared positive electrode material was evaluated using a CR2016 button cell. The negative electrode of the button cell was a metal lithium sheet with a thickness of 1 mm and a diameter of 15 mm; 0.16 g of the final products prepared in Examples 1-6, Examples 12-14, Examples 16-22, and the positive electrode materials of Comparative Examples 1-4, 0.02 g of conductive acetylene black, and 1 mL of PVDF N-dimethylpyrrolidone solution (PVDF concentration was 20 mg / mL) were weighed respectively, and a slurry was prepared after stirring; the slurry was then coated on an aluminum foil with a carbon coating on the surface, dried at 120°C in a vacuum oven, and then cut into a positive electrode sheet with a diameter of 14 mm using a punching machine, and the active material loading on the positive electrode sheet was 3-4 mg. When assembling the battery, a glass fiber separator from Whatman was used, and 1M lithium hexafluorophosphate electrolyte (solvents were EC and DMC, and the solvent volume ratio was EC:DMC=1:1) was used in a glove box. During assembly, oxygen and water vapor were both below 0.1ppm. The electrochemical test was performed using the CHI760e electrochemical workstation from Shanghai Chenhua and the LAND-CT2001C battery test system from Blue Electric. The test results are shown in Tables 1 and Figure 4-Figure 6 , Figure 8 .
[0132] Full battery performance test: The Na-W coated modified lithium cobalt oxide material prepared in Example 12, conductive carbon and PVDF were weighed in a weight ratio of 94:3:3 and mixed with NMP to prepare a positive electrode slurry, which was coated on aluminum foil on both sides to prepare a positive electrode sheet with a surface density of 14.5 mg cm per side. -2 The silicon-carbon negative electrode material, conductive carbon, dispersant sodium carboxymethyl cellulose and binder polyacrylic acid were weighed in a weight ratio of 90:5:1:4 and then mixed with water to prepare a negative electrode slurry, which was then coated on both sides of the copper foil to prepare a negative electrode sheet with a single-side surface density of 8.5 mg cm -2 ; The electrolyte is 1M lithium hexafluorophosphate solution, the solvent volume ratio is EC:DMC=1:1, about 3.5g (Ah) -1 , N / P ratio is controlled at 1.05-1.10, test results are shown in Figure 7 .
[0133] Table 1
[0134]
[0135]
[0136] from Figure 4 It can be seen that the initial specific capacity of the high nickel ternary cathode after coating modification is improved, and the first efficiency is also significantly improved. Figure 5It can be seen that the cycle stability of the high-nickel ternary positive electrode material after coating and modification is significantly improved. The capacity retention rate of the high-nickel ternary positive electrode material before modification is 77.5% after 200 cycles at a 1C rate. The capacity retention rate of the high-nickel ternary positive electrode material after modification is increased to 99% after 200 cycles at a 1C rate. Figure 6 It can be seen that the cycle stability of lithium cobalt oxide before and after coating modification at a high voltage of 4.6V is significantly improved. The capacity retention rate of lithium cobalt oxide before modification is 37% after 500 cycles at a 1C rate, and the capacity retention rate of the modified lithium cobalt oxide positive electrode material after 500 cycles at a 1C rate is 80.2%; and from Figure 7 The soft pack test data shows that the capacity retention rate of lithium cobalt oxide before coating modification is 87% after 30 cycles at a high voltage of 4.5V, and the capacity retention rate of the modified lithium cobalt oxide positive electrode material after 30 cycles at a high voltage of 4.5V is 98.1%, and the cycle stability is significantly improved; Figure 8 It can be seen that the cycle stability of lithium-rich manganese before and after coating modification is significantly improved. The initial capacity of lithium-rich manganese before modification is 205mAh / g at 1C rate, and the capacity retention rate is 62.5% after 300 cycles. The initial capacity of the modified lithium cobalt oxide positive electrode material is 250mAh / g at 1C rate, and the capacity retention rate is 89.8% after 300 cycles. Fig. 9 It can be seen that the cycle stability of the high-nickel positive electrode material is significantly improved before and after coating modification, and the performance of the two-step coating modification is slightly better than that of the one-step coating modification. The capacity retention rate of the high-nickel positive electrode material modified by the two-step coating method is 96.2% after 100 cycles, and the capacity retention rate of the high-nickel positive electrode material modified by the one-step coating method is 93.1% after 100 cycles.
[0137] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A multi-metal co-doped coated positive electrode material, characterized in that: The invention comprises a substrate and a coating layer located on the surface of the substrate, wherein the substrate is a lithium-containing layered oxide, and the coating layer is a layered oxide containing lithium and an alkali metal ion. n+ and high-valent metal ions B with valence ≥ 3 n+ "The alkali metal-based oxide heterostructure layer containing high-valent metals is formed by ion doping and structural reconstruction. The internal and external structural lattices are coherent and there is no obvious interface.
2. The multi-metal co-doped coated positive electrode material according to claim 1, characterized in that: The ratio of the sum of the mass of the alkali metal and the high-valent metal with a valence of ≥3 in the heterogeneous structure layer to the mass of the lithium-containing layered oxide is (0.002-0.6):1, preferably (0.02-0.2):1; And / or, the chemical formula of the lithium-containing layered oxide is Li x M y Q2, M is one or more of Ni, Co, Mn, Cu, Fe, Zn, Al and Cr, and Q is one or more of O, F, Cl, S, Se and N; And / or, the lithium-containing layered oxide is one or more of lithium cobalt oxide, a ternary positive electrode material and a lithium-rich manganese material; and / or, the coating layer has a thickness of 2-10 nm; And / or, the alkali metal ion A n+ for Na + and / or K + ; And / or, the high-valent metal ion with a valence of ≥3 is a transition metal ion with a valence of ≥3 and / or a main group metal ion with a valence of ≥3; the transition metal ion B with a valence of ≥3 n+ Preferably Ti 4+ 、Zr 4+ 、Ru 4+ , Nb 5+ 、 5+ 、Mo 6+ and W 6+ One or more of; the main group metal ion with a valence ≥ 3 is preferably In 3+ Sn 4+ and Sb 3+ One or more of .
3. A method for preparing a multi-metal co-doped coated positive electrode material, characterized in that: It includes the following steps: Method 1: (1) Li-containing layered oxide Li x M y A mixture of Q2 and a compound containing an alkali metal A is annealed to obtain a precursor; wherein the mass ratio of the alkali metal in the compound containing the alkali metal A to the lithium-containing layered oxide is (0.001-0.3):1; (2) the precursor and a high-valent metal ion B having a valence of ≥3 n+ A mixture of a metal salt and / or an oxide containing a high-valent metal B with a valence ≥3 is annealed; wherein the high-valent metal ion B containing a valence ≥3 n+ The mass ratio of the high-valent metal with a valence ≥ 3 in the metal salt and / or the oxide containing the high-valent metal B with a valence ≥ 3 to the lithium-containing layered oxide is (0.001-0.3): 1; Or, method 2: Lithium-containing layered oxide Li x M y Q2. Compounds containing alkali metal A and compounds containing high-valent metal ions B with a valence ≥ 3 n + wherein the mass ratio of the alkali metal in the compound containing the alkali metal A to the lithium-containing layered oxide is (0.001-0.3):1, and the high-valent metal ion B containing the valence ≥3 is 1:
1. n+ The mass ratio of the high-valent metal with a valence ≥3 in the metal salt and / or the oxide containing the high-valent metal B with a valence ≥3 to the lithium-containing layered oxide is (0.001-0.3):
1.
4. The method for preparing a multi-metal co-doped coated positive electrode material according to claim 3, characterized in that: The lithium-containing layered oxide is as described in claim 2; And / or, the alkali metal A is Na and / or K; And / or, the compound containing alkali metal A is one or more of a metal salt containing alkali metal A, a base containing alkali metal A and an oxide containing alkali metal A; The salt containing alkali metal A is preferably sodium carbonate, sodium bicarbonate, potassium carbonate or potassium bicarbonate; the base containing alkali metal A is preferably sodium hydroxide or potassium hydroxide; the oxide containing alkali metal A is preferably sodium oxide or potassium oxide; And / or, the mass ratio of the alkali metal in the compound containing the alkali metal A to the lithium-containing layered oxide is (0.001-0.2):1, for example, 0.005:1, 0.01:1, 0.02:1, 0.05:1 or 0.1:
1.
5. The method for preparing a multi-metal co-doped coated positive electrode material according to claim 3, characterized in that: The high-valent metal with a valence of ≥3 is a transition metal with a valence of ≥3 and / or a main group metal with a valence of ≥3, preferably a transition metal with a valence of ≥3; the transition metal with a valence of ≥3 is preferably one or more of Ti, Zr, Ru, Nb, Ta, Mo and W; the main group metal with a valence of ≥3 is preferably one or more of In, Sn and Sb; And / or, the high-valent metal ion B containing a valence ≥ 3 n+ The metal salt is a high-valent metal ion B containing a valence ≥ 3 n+ alkoxides and / or ammonium salts of, for example, tetrabutyl zirconate, tetrabutyl titanate, ammonium niobium oxalate, ammonium molybdate, ammonium tungstate, antimony nitrate or indium nitrate; And / or, the oxide containing the high-valent metal B with a valence ≥ 3 is tungsten oxide, molybdenum oxide, titanium oxide, zirconium oxide, niobium oxide, tantalum oxide, indium oxide, tin dioxide or antimony oxide; And / or, the high-valent metal ion B containing a valence ≥ 3 n+ The mass ratio of the high-valent metal with a valence ≥ 3 in the metal salt and / or the oxide containing the high-valent metal B with a valence ≥ 3 to the lithium-containing layered oxide is (0.001-0.2):1, for example, 0.005:1, 0.007:1, 0.009:1, 0.01:1, 0.02:1 or 0.1:
1.
6. The method for preparing a multi-metal co-doped coated positive electrode material according to claim 3, characterized in that: Method 1, in step (1), the annealing satisfies one or more of the following conditions: (1) The annealing temperature is 400-1000°C, preferably 500-800°C, such as 550°C, 650°C or 700°C; (2) The annealing time is 4-24 hours, preferably 6-24 hours, for example 10 hours, 15 hours or 20 hours; (3) The rate of heating to the annealing temperature is 1-10°C / min.
7. The method for preparing a multi-metal co-doped coated positive electrode material according to claim 3, characterized in that: In step (2) of method 1 and / or method 2, the annealing satisfies one or more of the following conditions: (1) Method 1, in step (2), the annealing temperature is 200-1000°C, preferably 400-800°C, for example 550°C, 650°C or 700°C; (2) Method 1, in step (2), the annealing time is 0.5-24h, preferably 8-24h; (3) Method 1, in step (2), the rate of heating to the annealing temperature is 1-10°C / min; (4) In method 2, the annealing temperature is 300-1000°C, preferably 400-800°C, for example 550°C, 650°C or 700°C; (5) In method 2, the annealing time is 0.5-24h, preferably 8-24h; (6) In method 2, the rate of heating to the annealing temperature is 1-10°C / min.
8. The method for preparing a multi-metal co-doped coated positive electrode material according to claim 3, characterized in that: Method 1: In step (1), the mixture is further subjected to micro-water mixing, solid phase mixing or liquid phase mixing before the annealing treatment; Wherein, the micro-water mixing preferably comprises the following steps: stirring and evaporating a solution containing the mixture; the solvent in the solution is preferably one or more of deionized water, ethanol, acetone, DMF, ethylenediamine and triethylamine; the amount of the solvent is preferably enough to immerse the solid material, and the ratio of the mass of the lithium-containing layered oxide to the volume of the solvent is more preferably (0.5-2) g / mL, such as 1 g / mL, 1.5 g / mL or 2 g / mL; Wherein, the solid phase mixing preferably comprises the following steps: grinding the mixture; Wherein, the liquid phase mixing preferably comprises the following steps: fully stirring the solution containing the mixture at 15-200° C., then performing solid-liquid separation and drying; And / or, in step (2) of method one and / or method two, the mixture is further subjected to micro-water mixing, solid phase mixing or liquid phase mixing before annealing.
9. A multi-metal co-doped and coated positive electrode material prepared by the preparation method according to any one of claims 3 to 8.
10. Use of the multi-metal co-doped coated positive electrode material as claimed in claim 1, 2 or 9 in a lithium ion battery.
Citation Information
Patent Citations
High-voltage positive electrode material capable of realizing structure reconstruction based on surface layer ion exchange reaction and preparation method of high-voltage positive electrode material
CN113921786A
Positive electrode material and preparation method thereof, positive plate and sodium ion battery
CN116154136A
Spinel-type lithium manganate compositely doped and modified by utilizing cations with different valence states and preparation method of spinel-type lithium manganate
CN116864666A
Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery
CN117038927A
High-low-valence element synergistically doped high-nickel ternary positive electrode material, preparation method thereof and application of high-low-valence element synergistically doped high-nickel ternary positive electrode material in high-voltage lithium ion battery
CN118173778A
Cited By
Layered transition metal oxide material mediated pre-sodium-modified material and application thereof
CN122338077A